274 Cerebrovascular events in takotsubo syndrome: short- and long-term outcome. Results from a multicentre-prospective registry. (8th December 2021) - Leopizzi, Alessandra; Santoro, Francesco; Mallardi, Adriana; Vitale, Enrica; Brunetti, Natale Daniele
Abstract: Aims: Several studies have shown that Takotsubo syndrome (TTS) secondary to neurological disorders is associated with higher rate of in-hospital complications. Imaging brain studies found that atrophy or damage of some regions and their altered connectivity with other brain regions are typical features of TTS patients. The aim of the study is to evaluate rates of in hospital and long-term Follow-up events in TTS patients with history or acute cerebrovascular events (CVE). Methods and results: 395 consecutive patients were enrolled in a multicentre prospective registry. History, clinical data, echocardiographic parameters and in-hospital and long-term follow-up events of all patients were evaluated. Prevalence of cerebrovascular events among TTS patients was 9.4% (num = 37). Compared to the control group, these patients were older (80 ± 7 vs. 71 ± 12, P = 0.01) and predominantly men (24% vs. 9%, P = 0.01). No differences in term of cardiovascular risk factors and left ventricular ejection fraction at admission and discharge were found among the two groups. The prevalence of physical stressor was higher in the CVE group (67% vs. 44% P = 0.01). The incidence of in-hospital adverse events was higher in the CVE than in the control one (70% vs. 29%), mainly driven by higher rate of Cardiogenic shock (19 vs. 8% P = 0.01) and in-hospital death (19 vs. 4%, P = 0.01). At long-term follow-up, patients in CVE group hat higher mortality rate (38% vs. 20% P = 0.01)). Patients presenting with acute CVE, 10 out of 37 patients (27%) when compared with chronic CVE had higher in-hospital mortality (40% vs. 11% P = 0.01). Conclusions: TTS patients with history or acute cerebrovascular events had higher rate of in-hospital events and death at long-term follow-up. Acute cerebrovascular events in the setting of TTS are featured with worst prognosis.